Estudo da durabilidade de geomembranas utilizadas na impermeabilização de reservatórios das barragens de rejeito de ouro - Leandro Sousa dos Santos (2014)
This work presents the evaluation of the High Density Polyethylene (HDPE) and Polyvinyl Chloride (PVC) geomembranes (GM), after exposure in waterproofing of reservoirs of the tailing dams of the gold mining company, located in the state of Bahia, northeast region of Brazil. The gold is the metal mined, which beneficiation process used for its separation of the mineral waste uses a set of physical and chemical operations. After all the beneficiation process the tailings deposition occurs in the dam, which foundation and slopes are waterproofing with geomembranes. The HDPE and PVC geomembranes used in this study have 1.5 and 0.8 mm thick, respectively, and were installed in field from 2006 to 2011. In this referred research, tests were performed on fresh geomembrane samples and samples directly exhumed from dams, allowing the comparison of the durability in both cases and thus conclude about the degree of aging of the geomembranes applied. Laboratory tests were carried out in order to aging the geomembranes under the same field conditions. Tests in weathering chamber for accelerate the process of aging the polymers were also performed. Regarding the laboratory tests the geomembranes were immersed in the dam fluid, also simulating the similar conditions, of temperature and exposure to UV rays, as were found in the dam. Tests of physical properties of the geomembranes (thickness, weight and density), thermogravimetric analysis, tensile tests and scanning electron microscopy of fresh geomembranes samples, of the samples obtained from the laboratory tests, from the weathering chamber and from samples directly exhumed from dams were also performed. The results of the analyses showed that the exhumed PVC and HDPE geomembranes presented a tendency of decreasing in deformability and increasing in stiffness, and presented some degree of degradation. The GM of PVC, however, showed a pronounced behavior in this sense. Some PVC samples also presented decreasing of weight after immersion in cyanide-containing fluid; however for some aging processes some samples were more ductile.